Розвиток дуальної форми освіти, як дієвого механізму підвищення якості підготовки фахівців - Ломейко, Олександр Петрович; Ломейко, Александр Петрович; Lomeiko, Oleksandr; Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Samoichuk, Kyryl; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Oleksiienko, Vadym (ТДАТУ імені Дмитра Моторного, 2020)
UK: Розглянуто основні аспекти організації і розвитку дуальної форми освіти в Таврійському державному агротехнологічному університеті імені Дмитра Моторного, наведено перелік нормативних документів і порядок організації та моделі здобуття освіти за дуальною формою навчання. EN: The basic aspects of the organization and development of the dual form of education at the Dmytro Motorny’s Tavria State Agrotechnological University are considered, the list of normative documents and the procedure of organization and model of obtaining the education by dual form of education are given.
Development of a dual education form as an effective mechanism for improving the quality of technicians training
Keywords: дуальна форма освіти; освітній процес; адаптація випускників; вимоги виробництва; професійні практичні компетенції; якість підготовки фахівців; співпраця з підприємствами; dual form of education; educational process; adaptation of graduates; production requirements; professional practical competences; quality of technicians training; cooperation with enterprises